Analisis Faktor-Faktor Yang Mempengaruhi Kualitas Laba (Studi Empiris Pada Perusahaan Property And Real Estate Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2019) - Fushy Dian Shantika Rumsawir; Paulus K. Allolayuk; Hastutie N. Andrianti (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2021)
This study aims to test whether the above factors affect the quality of profit. This research was conducted on property and real estate subsector manufacturing companies listed on the Indonesia Stock Exchange. This study also uses quantitative approach with research year from 2014 to 2019. Financial report data obtained through access to www.idx.co.id using purposive sampling method, so obtained 48 samples. The analysis method used is multiple linear regression analysis, with the help of IBM SPSS 21 program.This study used a constant value (α) of 5%. Based on the results of the study, the size of the company had a significant effect with a significant value of 0.001. While leverage, liquidity, managerial ownership and institutional ownership had no significant effect with a significant value of 0.051; 0,947; 0.414 and 0.594 and simultaneously, leverage, company size, managerial ownership and institutional ownership significantly affect the quality of profit.